EXTENT AND DETERMINANTS OF RURAL POVERTY IN PAKISTAN: ROLE OF ADOPTING RISK MANAGEMENT STRATEGIES - M. A.Iqbal; Qing Ping; M.Abid; A.Abbas; M. K. Bashir; Raza Ullah (Journal of Animal and Plant Sciences, 2018)
Poverty eradication has become one of the main agenda of development policies all around the globe. Besidesmanypoverty eradication programs, still, developing countries are trying hard to cope with poverty. Based on a household survey of 480 farm households, this study assesses the extent, degree of rural poverty among farm households in different districts of Punjab province, Pakistan. The study used Foster-Greer-Thorbecke ( FGT) approach to calculate level and extent of poverty and logistic regression method to identify the determinants of rural poverty among farm households in Punjab, Pakistan. The study revealed exciting findings and showed that more than half of the farm households in the study districts are living under the poverty line of $2 a day of them about one-tenth are earning even less than $1 a day. The study also found that use of different income sources in addition to agriculture not only reduced the level of poverty but also help farm households in reducing the depth of poverty. The study also found an inverse effect of education, off-farm income, farming area, annual unearned income, access to credit, number of animals and adaptation to various risks on poverty status of farm households. Further distance from input market and dependency ratio were positively associated with poverty status of farm households. about 40% of the population live under the poverty line
Keywords: Vulnerability; Adaptation; Development; Income distribution; Education.